2010
DOI: 10.1007/s11240-010-9884-4
|View full text |Cite
|
Sign up to set email alerts
|

HPLC and GC analyses of in vitro-grown leaves of the cancer bush Lessertia (Sutherlandia) frutescens L. reveal higher yields of bioactive compounds

Abstract: Lessertia frutescens L., commonly known as cancer-bush, is a medicinally reputed plant species indigenous to southern Africa. Field leaf extracts of this species are known to exhibit many curative properties. However, little is known about the bioactive compounds that are present in in vitro leaf extracts and seed extracts. The objective of this study was to verify the presence of and quantify L-canavanine, gamma amino butyric acid (GABA), arginine and D-pinitol in the seeds, field leaves and in vitro leaves o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 42 publications
1
21
0
Order By: Relevance
“…Proline, L-asparagine, and alanine were the most abundant amino acids and collectively represent almost 60% of total amino acid content; however, not all samples contained all the amino acids. e content of L-canavanine, arginine, GABA, and D-pinitol in seeds, �eld leaves, and in vitro leaves of S. frutescens was quanti�ed by Shaik et al [158]. e results revealed that the secondary metabolites signi�cantly differed depending on the source.…”
Section: Phytochemistry and Biologicalmentioning
confidence: 98%
“…Proline, L-asparagine, and alanine were the most abundant amino acids and collectively represent almost 60% of total amino acid content; however, not all samples contained all the amino acids. e content of L-canavanine, arginine, GABA, and D-pinitol in seeds, �eld leaves, and in vitro leaves of S. frutescens was quanti�ed by Shaik et al [158]. e results revealed that the secondary metabolites signi�cantly differed depending on the source.…”
Section: Phytochemistry and Biologicalmentioning
confidence: 98%
“…These extracts are also reported to inhibit the action of human immunodeficiency virus (HIV) target enzymes (Hartnett et al 2005) and decrease cancerous cell growth (Stander et al 2009), which are purported to be the result of the action of L-canavanine. Research in our laboratory has shown that the yields of medicinal phytocompounds are higher in in vitro leaf extracts than in field leaf or seed extracts (Shaik et al 2010a). Rout et al (2000) reported that medicines derived from plant sources are popular worldwide and, therefore utilized as pharmaceuticals on the global scale.…”
mentioning
confidence: 99%
“…leaves, stems etc.) from which the extract is derived (Shaik et al, 2010). At this time, no single molecular pathway explaining the effects observed in studies investigating the therapeutic potential of S.…”
Section: Discussionmentioning
confidence: 99%
“…When taking into account the fact that a single pharmacologically active ingredient responsible for the varied effects of S. frutescens has not been isolated and the differing efficacy of ethanolic and aqueous extracts, it becomes apparent that the cumulative combination of the bioactive compounds in plant extracts (Shaik et al, 2010) must be responsible for the promising antiproliferative effects. The concentrations of each of the potentially therapeutic compounds is, to a large extent, dependent on the location (regional differences) and growth conditions (soil conditions, UV exposure etc.)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation